2016
DOI: 10.1123/pes.2015-0231
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Balance and Muscle Strength, Power Performance in Male Youth Athletes of Different Maturity Status

Abstract: The associations between balance and muscle strength/power measures in youth athletes that increase with maturity may imply transfer effects from balance to strength/power training and vice versa in youth athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 0 publications
6
69
1
1
Order By: Relevance
“…Our polymorphisms selection has been performed in relation to muscle function and performance phenotypes, but not to specific polymorphisms previously related to growth and maturation, which we suggest for future studies performed on adolescents. The maturation status has been found to have effect on functional movement including SL (50) and the muscle strength and power performance (17). Our phenotype results (without considering anthropometry in Table 4) showed no difference between pre and post PHV young male (Table 7), which is in accordance with previous studies where e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Our polymorphisms selection has been performed in relation to muscle function and performance phenotypes, but not to specific polymorphisms previously related to growth and maturation, which we suggest for future studies performed on adolescents. The maturation status has been found to have effect on functional movement including SL (50) and the muscle strength and power performance (17). Our phenotype results (without considering anthropometry in Table 4) showed no difference between pre and post PHV young male (Table 7), which is in accordance with previous studies where e.g.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, sprinting is a series of rapid, unilateral landings and propulsions which would place greater challenges on the balance capabilities of the individual. Balance is another important contributor to SSC and sprint performance especially in youth (Hammami et al, 2016a). Balance affects force, power output and movement velocity (Anderson and Behm, 2005; Drinkwater et al, 2007; Behm et al, 2010a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Since balance and coordination are not fully mature in children (Payne and Isaacs, 2005), the effectiveness of plyometric training could be adversely affected. Hammami et al (2016a) reported large-sized correlations between balance measures and proxies of power with youth ( r = 0.511–0.827). These correlation coefficients were greatest with the more mature post-peak height velocity (PHV) youth, suggesting that the poorer postural control of the less mature pre-PHV and PHV youth had negative consequences upon power output.…”
Section: Discussionmentioning
confidence: 99%
“…Central to the YPD model is the development of muscular strength, which should be targeted throughout youth, for both males and females, due to its underpinning of performance capabilities. Indeed, the importance of muscular strength in supporting young athletes' performances has been demonstrated on tasks such as change of direction [8,9], vertical jump [9][10][11], leg stiffness [11], sprint ability [9,12] and balance [13]. Accordingly, as muscular strength is an integral component of youth strength and conditioning programs for performance enhancement [2] and also for reducing the risk of sport-related injuries [14], training modalities that can further develop this component are necessary.…”
Section: Introductionmentioning
confidence: 99%